La relevancia de respetar el derecho a la jornada máxima de trabajo en la actualidad - Ulloa Millares, Daniel (2019)
The right to a maximum working hours per day (or week) was recognized a century ago in the first convention of the International Labour Organization and has been included in the most important international conventions adopted by Peru. However, it has not been able to consolidate, even though its relevance has not changed. We believe that the right to digital disconnection is a confirmation of the importance of said concept, which we shall describe in this work.